Program Indonesia Sehat dengan Pendekatan Keluarga (PIS-PK) di Kecamatan Babakan Madang, Kabupaten Bogor Tahun 2019 - Dion Zein Nuridzin; Martya Rahmaniati; Tris Eryando; Rico Kurniawan; Retnowati Retnowati (STIKes Surya Global Yogyakarta, 2020)
Background of Study: Currently, Indonesia has not succeeded in achieving a “Healthy Indonesia” as desired in the National Long-Term Development Plan. Realizing this problem, the government created Healthy Indonesia Program with a Family Approach (Program Indonesia Sehat-Pendekatan Keluarga or PIS-PK). This study aims to determine the coverage of 12 PIS-PK indicators and the category of healthy family index (HFI). Methods: This study used a cross-sectional study. The data source comes from the 2019 Demographic Health Surveillance System in Babakan Madang subdistrict, Bogor Regency which was collected by health cadres. Data analysis was carried out on 19,330 families using SPSS and mapping using Arcview. Results: Indicators of PIS-PK with high coverage are children under five receiving growth monitoring (96.9%), families having access to clean water facilities (88.9%), and families having access to or using healthy latrines (87.8%). A total of 10.3% were healthy families, 64.7% were “pra-sehat” families, and 25.0% were unhealthy families. All villages in Babakan Madang Subdistrict are categorized as unhealthy villages (HFI